A biometric smart card based remote user authentication for telecare medicine information system - Suratose Tritilanunt (2020)
© 2019 Association for Computing Machinery. Telecare medicine information system (TMIS) using authentication protocols as a first defensive line to prevent an unauthorized user to illegally access into a system has been used for many years. Even though in the past decade there were many security researchers proposing some development of authentication scheme, most of them were still susceptible to several kinds of attack. Last year, Quan et al. proposed a secure and efficient biometric smart card based user password authentication scheme that be able to resist against various well-known attacks, for example, off-line password guessing and impersonation attacks. This work demonstrates the attack to figure out that the proposed scheme is still not be able to resist a man-in-the-middle attack. Finally, this work proposes some suggestions to fix vulnerabilities and improve a biometric smart card based authentication scheme for a telecare medicine information system. By presenting an analysis of protocol security, this new improvement provides a more efficient and secure authentication scheme as well as protects user’s credentials at the same time.